ITLN in diploid hybrid fish (Carassius auratus cuvieri ♀ × Carassius auratus red var ♂) is involved in host defense against bacterial infection. (February 2020) - Luo, Sheng-Wei; Luo, Kai-Kun; Liu, Shao-Jun
Abstract: Hybrid genotypes in fish may be less susceptible to pathogenic infection. ITLN, a novel lectin, not only exhibits a regulatory role in pathogenic infection, but also participates in the regulation of teleostean immunity. In this study, ORF sequence of WR-ITLN was 945 bp and encoded 314 amino acid residues. Tissue-specific analysis revealed that the highest expression of WR-ITLN was observed in liver. Aeromonas hydrophila challenge can sharply increased WR-ITLN mRNA expression in liver, kidney and spleen. The purified WR-ITLN protein can directly bind to A. hydrophila and S. agalactiae, reduce their relative bacterial activity and limit bacterial growth in vitro in the presence of Ca 2+ . In addition, the treatment of WR-ITLN + Ca 2+ can restrict bacterial dissemination in vivo and attenuate production of pro-inflammatory cytokines. These results indicated that WR-ITLN can confer protection against bacteria-stimulated MyD88-dependent pro-inflammatory cytokines activation in a Ca 2+ -dependent manner. Highlights: We characterized a novel ITLN gene in hybrid crucian carp. The up-regulation of WR-ITLN was observed following bacterial challenge. WR-ITLN can bind to gram-positive or gram-negative bacteria and restrict their growth in the presence of Ca 2+ . Combined treatment of WR-ITLN + Ca 2+ can diminish bacteria-stimulated inflammatory response.